Student leadership experience : a phenomenological analysis from the perspective of student leaders in university student organizations - Gowthaman, Anamika (2019)
The aim of this study is to explore the lived experiences of the student leaders from different student organizations at a university. This study was designed to better understand the phenomenon of student leadership from the perspectives of the student leaders themselves. In order to understand the essence of the experience, the motivation to seek it and the outcome or effects of the leadership experience after completing it were taken into consideration. The goal of the study is not to produce a generalized perspective on the phenomenon, but to present the experiences as lived by the participants acknowledging their subjectivity. To answer these questions, a phenomenological research method was adopted as it focuses on understanding the lived experience in order to get a better understanding of the phenomenon in question. This qualitative study is based on empirical evidence. The data was gathered from interviews with eight student leaders, who were studying during their leadership experience. The context of the study is set at the university level. The findings show that the essence of their collective experiences revolve around two key aspects 1) self-development and 2) connection with people. The experiences had both positive and negative moments and the student leaders faced various challenges which led to learning points. The reasons that motivated the students to join student organizations and to take on the responsibilities of student leadership seem to be fulfilled after the experience. This study presents a closer and deeper view of the leadership experiences the participants have had, from their perspectives. It brings out an important perspective of the experience being a valuable learning experience which is positively recommended by the participants to fellow students.